PAI and Global Issues: Multiculturalism and Social Justice - Agung Cahya; Muhammad Zuhdi; Bobi Erno Rusadi (Penerbit Presisi Pustaka, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) in responding to the global issues of multiculturalism and social justice in the era of globalization. The study uses a qualitative approach with library research. Data are sourced from the Qur'an, hadith, as well as relevant scientific literature and educational policy documents. Data collection was conducted through data analysis studies using descriptive-analytical and comparative content analysis. The results show that PAI has a strategic role in instilling the values ​​of tolerance, humanity, and social justice as an integral part of Islamic teachings. These values ​​are rooted in the principles of monotheism, equality, and social concern. This study concludes that the integration of multiculturalism and social justice in PAI learning is important for developing inclusive, moderate, and globally civilized students.